Penyisihan Zat Organik Dan Warna Pada Air Gambut Dengan Koagulan Alami Campuran (Biji Jagung, Biji Kelor Dan Biji Semangka) - Rehansyah, M Akhbar; HS, Edward; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Impurities in peat water in the form of high organic concentrations and dark brown to blackish color that cause negative impact on health if consumed in the long term. This condition encourages the emergence of new studies in peat water treatment. One of them by using natural coagulant with coagulation and flocculation process. In this study will utilize moringa seeds, corn kernels and watermelon seeds in comparing the effectiveness of single natural coagulant and natural coagulant mixture by varying the mass and natural coagulant mixture. The results showed that the parameter of organic matter and color was 107,1 mg / l with mass of 0.5 gr and 76 Pt-Co with mass of 0.5 gr for single natural coagulant of Moringa seed powder, and 201,1 mg / l with mass 0.5 gr and 188 Pt-Co with a mass of 2.0 grams for natural coagulant mixture of moringa and corn powder.Keywords: impurities, organic substances, color, moringa seeds, corn kernels, and watermelon seeds